CAFF Map No.29 - Distribution of wolf Canis lupus in the Northern Hemisphere - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (2001)
CAFF Map No 29 - Distribution of wolf Canis lupus in the Northern Hemisphere, 2001